Charakter dyskusji politycznej na portalach informacyjnych. Studium przypadku - Pawlak, Piotr (Studia Europaea Gnesnensia, 2016)
The article offers a two-dimensional analysis of the discussion forums on Polish news and information websites, as a public space of political discourse. The author employed statistical analysis for quality variables and interpretation of narrative patterns. The primary aim of the study was to determine the nature of debate in the area under consideration, in the context of exacerbated political dispute. The obtained results were compared with previous findings of this author.